2000
DOI: 10.1097/00007632-200002010-00018
|View full text |Cite
|
Sign up to set email alerts
|

A Radiostereometric Analysis of Movements of the Sacroiliac Joints During the Standing Hip Flexion Test

Abstract: The small movements registered support the theory of form and force closure in the sacroiliac joints. The self-locking mechanism that goes into effect when the pelvis is loaded in a one-leg standing position probably obstructs the movements in the sacroiliac joints. Therefore, the standing hip flexion test cannot be recommended as a diagnostic tool for evaluating joint motion in the sacroiliac joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
91
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 22 publications
4
91
1
3
Order By: Relevance
“…10 In a review of SIJ anatomy and biomechanics, motion occurring at the SIJ was reported to be a combination of rotation and translation that did not occur around a simple axis. 11 The motions available at the SIJ have been repeatedly found to be small, 12,13 not exceeding 2-3° or 1-2mm. 11 The SIJ has been implicated as a common source of LBP.…”
Section: Introductionmentioning
confidence: 98%
“…10 In a review of SIJ anatomy and biomechanics, motion occurring at the SIJ was reported to be a combination of rotation and translation that did not occur around a simple axis. 11 The motions available at the SIJ have been repeatedly found to be small, 12,13 not exceeding 2-3° or 1-2mm. 11 The SIJ has been implicated as a common source of LBP.…”
Section: Introductionmentioning
confidence: 98%
“…Different radiographic modalities have been used to measure movement in the sacroiliac (SI) joint objectively [7,12,15], whereas five studies have used RSA to evaluate movement between the sacrum and the ilium [16][17][18][19][20]. With RSA, a maximum rotation of 3.6°has been measured and the translation never exceeded 2 mm in the SI joint, which is less movement than other methods have revealed [5], and for this reason the method has been questioned [3].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have measured movement between the sacrum and the ilium with dorsally placed markers [16][17][18][19][20]. In these studies, the markers were placed close to the joint line, and because of the flat anatomy of the bones, the markers become collinear (in the same plane).…”
Section: Introductionmentioning
confidence: 99%
“…These are very large numbers relative to some very conservative contemporary estimates of sacroiliac mobility, such as those of Sturesson et al [31][32][33] and those appearing in a review article by Goode et al 34 However, the 1.5 in of artificial LLI created by Pitkin and Pheasant is also very large compared with the amount of LLI produced or found in other studies herein reviewed, some of which showed a linear, monotonic dose response of pelvic torsion to induced LLI. Moreover, the mean amount of torsion reported by them is within shouting distance of other modern investigators who have reported far more torsion to occur, such as a clinical study by Cibulka et al, 35 a cadaveric study using advanced imaging by Smidt et al, 36 another clinical study by Smidt et al, 37 and the Drerup and Hierholzer 20 study included in this review.…”
Section: Study Observationsmentioning
confidence: 86%